Rehabilitasi Pasca Covid-19 Menjadi Kunci Untuk Meningkatkan Kesehatan Pada Masyarakat - Sekar Wulan Apriliasari; Raihany Sholihatul; Ida Lisni; Aulia Nurfazri Istiqomah; Wahyu Wahdana (Jurnal Abdi Masyarakat Kita, 2022)
The pandemic due to Covid-19 can cause problems in Indonesia, especially on health problems that are mostly experienced by people who located in the Sukarindik Village area, Tasikmalaya City. Therefore, in order to solve the problem that occurred in Sukarindik Village, Tasikmalaya, carried out the 2021 Thematic PPM KKN activity program through post-Covid-19 physical rehabilitation measures in the form of breathing exercises, relaxation, exercise, exercise and jogging. The implementation of these activities is carried out online with the method of implementing webinar activities using the Zoom application. The results showed that the people of Sukarindik Village would carry out regular exercise every week to maintain physical fitness, improve heart and lung function. In conclusion, education related to post-covid-19 physical rehabilitation for the community is important. Because it can accelerate the healing of symptoms exposed to COVID-19, improve the quality of daily activities and improve health in the Sukarndik Village Community.